Saturated sliding mode control with limited magnitude and rate - Wang, Siyi; Gao, Yabing; Liu, Jianxing; Wu, Ligang (IET control theory & applications, 2018)
This study is concerned with the sliding mode control design subject to actuator saturation. The actuator saturation is formulated with the rate limitation and the standard magnitude limitation. Both the saturated sliding mode control approaches against the known and the unknown bounded uncertainties are discussed. The stability analysis for the resulting overall closed-loop systems is conducted. Moreover, several optimisation conditions are established to estimate the attraction domain of the saturated system under the designed controllers, by determining the invariant set of the system. Finally, simulation examples are shown to illustrate the proposed control design scheme.